Evaluation of Pavement Performance due to Overload Single-Trip Permit Truck Traffic in Wisconsin. (1st August 2018) - Titi, Hani H.; Coley, Nicholas J.; Latifi, Valbon
Abstract : This study investigated the impacts of overweight (OW) permit truck traffic on flexible pavement performance in Wisconsin using field investigation and analysis utilizing the AASHTOWare Pavement ME Design software. A database of overweight single-trip permit truck records was analysed to produce a network of Wisconsin corridors heavily travelled by OW trucks. Four Wisconsin highways were selected for investigation due to high levels of OW truck traffic. The research included field work (traffic counts and visual pavement surface distress surveys) and AASHTOWare Pavement ME Design. Comprehensive analyses were conducted to evaluate pavement performance due to normal traffic loads as well as normal traffic loads plus the OW truck traffic loads. The use of mechanistic-empirical (ME) pavement analyses provided a methodology for estimating the proportion of pavement deterioration attributable to OW truck traffic. OW axle load distributions were developed and integrated with baseline truck traffic levels to develop axle load spectra and other traffic input parameters for the ME pavement analysis. The predicted total pavement deterioration levels from the AASHTOWare Pavement ME Design software were generally consistent with the levels of deterioration observed. The proportion of pavement damage and deterioration attributable to OW truck traffic was predicted to constitute a relatively minor proportion of total deterioration, with most distress indices showing relative increases of approximately 0.5% to 4%, with a few outliers. However, due to the small proportion of OW vehicles relative to the overall traffic levels, the OW vehicles were generally predicted to cause up to ten times the per-truck damage as compared with a typical legal-weight truck, depending on the distress mode and the test site.